A rare case of mucinous adenocarcinoma of appendix presenting as acute small obstruction - Bhavsar, Uchit H.; Agarwal, Bhavdeep; Parmar, Kirit D.; Parikh, Samir G. (International Surgery Journal, 2025)
Mucinous appendiceal neoplasms are rare, occurring in <0.3% of appendectomies, often presenting incidentally. A 61-year-old female with periumbilical pain and vomiting was diagnosed with small bowel obstruction and mucinous adenocarcinoma of the appendix. Imaging showed bowel thickening and obstruction. Surgery revealed a fibrous band, serosal tears, and appendicitis with appendicolith. Histopathology confirmed adenocarcinoma with perineural invasion. Despite intervention, the patient succumbed to septicemia and multiple organ dysfunction syndrome (MODS). Appendiceal tumors are often incidental, requiring computed tomography (CT) for diagnosis. Right hemicolectomy is standard treatment. Early recognition and surgical management are key to improving prognosis in these rare cases.